An insight into Youth Unemployment in Indonesia - Ayuningtyas Yanindah (Politeknik Statistika STIS, 2021)
Youth unemployment in Indonesia has continued to remain at a high level relative to other age categories for several years. The case of Indonesia’s youth unemployment is grave with the presence of a low workforce participation rate, informal employment, and higher unemployment rates in young people compared with adults. Due to the lack of research on a country-wise view of youth unemployment, this study focuses on providing a much better understanding of the youth unemployment problem in emerging countries, especially Indonesia. The main aim of the paper is to bridge the research gap on youth unemployment with reference to microeconomic determinants, such as educational background and participation in training. This study utilized the August 2019 data of SAKERNAS (Survei Angkatan Kerja Nasional) and analyzed the data using the logistic regression method. Logistic regression is a special econometric model where the dependent variable is considered categorical and dichotomous (binary); in this case, it was unemployed (1) or working (0). The study found that training participation has a negative correlation with youth unemployment, while educational attainment generates mixed results.